Fatigue of additively manufactured 316L stainless steel: The influence of porosity and surface roughness. Issue 9 (19th July 2019) - Solberg, Klas; Guan, Shuai; Razavi, Seyed Mohammad Javad; Welo, Torgeir; Chan, Kang Cheung; Berto, Filippo
Abstract: The fatigue behaviour of additively manufactured (AM) 316L stainless steel is investigated with the main emphasis on internal porosity and surface roughness. A transition between two cases of failure are found: failure from defects in the surface region and failure from the internal defects. At low applied load level (and consequently a high number of cycles to failure), fatigue is initiating from defects in the surface region, while for high load levels, fatigue is initiating from internal defects. Porosities captured by X‐ray computed tomography (XCT) are compared with the defects initiating fatigue cracks, obtained from fractography. The fatigue data are synthesised using stress intensity factor (SIF) of the internal and surface defects on the fracture surface.